PENGARUH APLIKASI LIMBAH (Decanter solid) PABRIK KELAPA SAWIT TERHADAP PERTUMBUHAN VEGETATIF SERTA KADAR KLOROFIL DAUN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI PEMBIBITAN UTAMA - Saroha Manurung; Aulia Juanda DJS (Jurnal Agro Estate, 2021)
Oil palm is a plantation crop that has an important role in Indonesia today. This plant is a plant that produces vegetable oil and its derivative products. This study aims to determine the effect of solid decanter waste application on the vegetative growth of oil palm seedlings (Elaeis guineensis Jacq). This research was conducted in the research area of the Medan College of Agricultural Agribusiness (STIPAP) from January - July 2020. This study used a non factorial randomized block design (RBD) consisting of S0: Without decanter solid treatment, S1: 0,5 kg decanter solid, S2: 1,0 kg decanter solid, and S3: 1,5 kg decanter solid. Parameters observed were plant height, number of leaves, stem girth, leaf chlorophyll content, shoot wet and dry weight, root wet and dry weight. The data obtained were analyzed statistically with analysis of variance (ANOVA) with further test of LSD 5%. The treatment of decanter solid application has a significant effect based on statistical tests on the vegetative growth of oil palm seedlings, namely on the height of the seeds and stem circumference with the value of F-count seed height > F-Table 0,5% at 8 MSA and F-Count on stem circumference > F- Table 0,1% at 16 MSA and 20 MSA, while the number of leaves, shoot wet and dry weight, root wet and dry weight and leaf chlorophyll content showed no significant effect, the best treatment was S3 with a dose of 1,5 kg/polybag.